Effects of different fertilizers formulas on the growth and development of leaf mustard, Brassica juncea / Nur Hasyimah Ramli and Zuhrah Aini Sulaiman - Ramli, Nur Hasyimah; Sulaiman, Zuhrah Aini (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Fertilizers are the most important and complex nutrients for crop plants in particular for grain yield and quality. The composition of the fertilizer as well as the essential elements that influence the growth of the crop need to be clearly identified. Due to that, this study was carried out to investigate the effect of different fertilizer formulation on the leaf mustard (Brassica juncea) growth. High nitrogen, phosphorus and potassium fertilizers were used to investigate their effects on the morphometric size of the leaves, plant height and the leaf area index of the leaf mustard. Results showed that the application of different formulation of fertilizer improves the growth of leaf mustard compared to control. Leaf mustard with the high phosphorus treatment recorded an increase in plant height and the leaf area index (LAI). Lamina length (LL) range is shown between phosphorus and control (1.11 cm), while the range of lamina width (LW), left width (WL) and right width (WR) are between potassium and control about 0.57 cm, 0.28 cm and 0.28 cm, respectively. Overall, there is a significant difference between the leaf mustard leaves in different high element fertilizers compared with all of the variable, F (15,1024) = 29.26, p<0.05. However, the highest mean (in cm) in height was obtained in high phosphorus (16.64) followed by high potassium (16.50), control (16.41) and high nitrogen (16.35) fertilizers with a mean range of 0.29 cm (F (3,176) = 0.47; p>0.05, no significant difference). The highest mean in LAI was obtained when treated with a high phosphorus fertilizer (0.47 m2). The mean difference of LAI of high phosphorus compared to high potassium, high nitrogen and control is 0.02 m2, 0.08 m2 and 0.12 m2. There is no significant differences between the LAI in different high element fertilizers with F (3,176) = 0.15; p>0.05. Further study should be conducted to determine the effects of different fertilizers on the growth of other vegetables and fruit quality.